Perbuatan Fraud Dilihat Dari Perspektif Pasal 1365 KUH Perdata - Fitia Maulidia Rahma; Arief Suryono (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This scientific work discusses acts of fraud committed by insureds which often occur in the insurance industry in Indonesia. This action violates Article 1365 of the Civil Code concerning Unlawful Actions (PMH). This research is normative legal research which has prescriptive and applied research characteristics. From this research, it was concluded that fraudulent claims can be said to be unlawful if analyzed according to the elements of unlawful acts.